Method Development and Validation of Curcuminoids in Curcuma Angustifolia Roxb. By RP-HPLC and Its Antifungal Activity: LifeScience-Herbal Chemistry - P Warrier, Pravith; R Badole, Madhavi (International Journal of Life Science and Pharma Research, 2023)
Curcuma angustifolia Roxb., a rhizomatous herb, belongs to the Zingiberaceae family of plants. The species is rich innutrients and is used mostly as a source of starch for Indian dishes and medicines. The published research articles for themeasurable estimation of components in Curcuma angustifolia Roxb. rhizomes are very scarce. The present study aimed to developa quantitative analysis method for estimating the constituents in the methanolic extract of Curcuma angustifolia Roxb. rhizome andto investigate its biological activity. Within the context of this challenge, the current work is a unique effort that recommends ahigh-performance liquid chromatography (HPLC) method for estimating curcuminoids, namely curcumin, demethoxycurcumin,and bis-demethoxycurcumin, present in the methanolic extract of Curcuma angustifolia Roxb. rhizome. A reverse-phase HPLCmethod was developed to estimate curcuminoids in the extract. The method was validated and found to be precise, sensitive,specific, linear, accurate, and robust. The method validation study's findings demonstrated the method's suitability for routine use.The HPLC method was successfully applied to a marketed formulation containing rhizome powder from Curcuma angustifolia Roxb.as one of its constituents. This study investigates the antifungal activity of the methanolic extract in vitro using an agar well diffusionassay method. A minimum inhibitory concentration (MIC) was established, and the antifungal activity was evaluated against Candidaalbicans and Candida glabrata with fluconazole as the standard reference. The development and validation of an HPLC method fortesting curcuminoids in Curcuma angustifolia Roxb. rhizome and the evaluation of rhizome extract antifungal activity are excellentexamples of herbal medicine quality control in its entirety. The in vitro antifungal activity results reaffirm the usage of Curcumaangustifolia Roxb. as a source of antifungal agents. They can lead to the developing of new herbal medicines in the coming days.